Evolution of Career Services in Higher Education. Issue 148 (December 2014) - Dey, Farouk; Cruzvergara, Christine Y.
Abstract : Socioeconomic changes, technological advances, and generational trends have been the impetus behind every major paradigm shift in the delivery of career services in higher education during the past century, including the one taking shape today. This chapter will provide an overview of the changing nature and emerging trends that are shaping the future of career services in higher education.